Akses UMKM Terhadap Pembiayaan Mikro Syariah dan Dampaknya Terhadap Perkembangan Usaha : Kasus BMT Tadbiirul Ummah, Kabupaten Bogor - Lukytawati Anggraeni; Herdiana Puspitasari; Salahuddin El Ayyubi; Ranti Wiliasih (AL-MUZARA'AH, 2013)
Micro, Small and Medium Enterprises (MSMEs) have a big contribution for Indonesia's gross domestic product and employment. Most MSMEs face capital constraints and limited access to formal financial institutions. Baitul Maal Wat Tamwil (BMT), which is one of the Islamic microfinance institutions, can be a solution to capital constraints faced by MSMEs. The study aims to analyze the MSME access to get the financing and the impact of BMT to their business development. The primary data is obtained from interviewing 45 respondents, i.e 30 respondents who receive funding from the BMT and 15 controlled respondents who do not receive funding in Bogor. MSME access to the BMT Islamic financing is analyzed by logistic regression logit model while the method used is multiple linear regression of Ordinary Least Square (OLS) in order to analyze the impact of BMT on the development of business. Logit regression results indicate that dummy business type, age, business turnover and deposits dummy, are the factors influencing MSME access to BMT financing. BMT financing has increased the MSME profit by 6.21 percent with an average of Rp 79.12 million to Rp 84.03 million per year. Based on the results of multiple linear regression of OLS, BMT financing has positive and significant impact on the change in business profits.